(untitled) (Research, Society and Development, 2023)
In Brazil most fruits have a rapid maturation process. An alternative to preserve these fruits are kefir-based edible coatings, which have high antimicrobial activity. This work aims to develop edible coatings using kefir yogurt, applied to apples and grapes to analyze the increase in shelf life. Two formulations of coatings with kefir yogurt (0.5 liter and 1 liter) were obtained and applied to the fruits. They were stored for a period of eleven days and submitted to physical-chemical and microbiological analyzis. The obtained results demonstrated that the coating with 1L of kefir yogurt, made the apples and grapes, together with the refrigeration, achieve a lower percentage of mass loss. In the grapes, the coating with 0.5l at room temperature was what obtained the best results for pH (3.06) and acidity (13.29 mL NaOH.100 g-1), both of which had a significant difference from the other samples. As for the apples, the same coating at room temperature showed a value of 4.42 for pH, being significantly equal to the other samples, and 0.63 for acidity, being significantly different from the other samples. For the microbiological analyses, the coating with 1l of kefir yogurt obtained better results for the microbiological control of apples and for the grapes the coating with 0.5L obtained better results. Thus, it is concluded that coatings based on kefir yogurt were effective, in this study, to preserve apples and grapes for a prolonged period.